Ruo2 uniformly supported w03 self-supporting catalyst electrode, preparation method and application thereof

By uniformly loading RuO2 onto the surface of WO3 nanowires to form a self-supporting catalyst electrode, the stability problem of Ru-based catalysts in acidic environments is solved, achieving a highly efficient acidic oxygen evolution reaction, which is suitable for PEM water electrolysis hydrogen production technology.

CN117802522BActive Publication Date: 2026-11-06HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410006856.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-03
Publication Date
2026-11-06
Estimated Expiration
2044-01-03

AI Technical Summary

Technical Problem

Existing Ru-based acidic oxygen evolution catalysts exhibit poor stability in PEM electrolyzers, making it difficult to meet the requirements of industrial applications and limiting the development of PEM water electrolysis for hydrogen production technology.

Method used

A stepwise hydrothermal-immersion-oxidation method was used to uniformly load RuO2 on the surface of WO3 nanowires to form a self-supporting catalyst electrode, and the Ru-OW synergistic effect was used to improve catalytic activity and stability.

Benefits of technology

The RuO2/WO3 self-supporting catalyst achieved high catalytic activity and long-term stability under acidic conditions. The overpotential at a current density of 10 mA cm-2 was lower than that of commercial RuO2, and it operated stably for more than 200 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117802522B_ABST
    Figure CN117802522B_ABST
Patent Text Reader

Abstract

This invention relates to a RuO2-uniformly loaded WO3 self-supporting catalyst electrode, its preparation method, and its application in oxygen desorption via acidic water cracking, belonging to the field of inorganic functional materials technology. First, a substrate is immersed in a tungsten source aqueous solution. Then, nanorod-shaped WO3 nanowires are formed on the substrate using a one-step hydrothermal method. Next, the substrate is immersed in a Ru source aqueous solution to adsorb Ru ions. Finally, oxidation in air yields a RuO2-uniformly loaded WO3 self-supporting catalyst electrode. The tungsten source can be ammonium metatungstate, tungsten chloride, sodium metatungstate, or sodium tungstate; the Ru source can be ruthenium chloride, ruthenium acetate, or ruthenium acetylacetonate; and the substrate can be carbon paper, carbon cloth, graphite sheet, titanium mesh, or titanium sheet. This invention loads RuO2 material onto the WO3 surface, which not only allows for uniform distribution of RuO2 at the nanoscale but also improves the stability of RuO2. The current density reaches 10 mA cm⁻¹. ‑2 At that time, the required overpotential is 203mV, and it can operate stably for more than 200 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic functional materials technology, specifically relating to a RuO2 uniformly loaded WO3 self-supporting catalyst electrode, its preparation method, and its application in acidic water cracking for oxygen desorption. Background Technology

[0002] Proton exchange membrane (PEM) electrolyzers utilize a proton exchange membrane to conduct protons to the electrolyte and isolate gases generated on both sides of the electrodes. This results in a low system resistance, significantly improving electrolysis efficiency and enabling high current density (>1 A cm⁻¹). -2 The PEM (Polymer Evolution of Hydrogen) electrolysis technology offers advantages such as high-quality hydrogen and a compact electrolyzer size. More importantly, it allows for rapid start-up and power regulation, perfectly suited to the volatility of renewable energy sources. Catalysts are crucial materials in the PEM water electrolysis reaction, especially catalysts for the oxygen evolution reaction (OER). Due to the strong acidity of the proton exchange membrane and the high anodic electrolysis voltage required for PEM water electrolysis, the catalyst must be able to operate stably for extended periods in strong acid and oxidizing environments, significantly limiting the range of catalytic materials that can be selected. Currently, the most widely used catalyst in commercial PEM electrolyzers is the precious metal iridium dioxide (IrO2), but its high cost and low reserves limit its large-scale application. Therefore, developing efficient, stable, and low-cost non-Ir-based OER catalysts is a key research focus in the development of PEM water electrolysis for hydrogen production technology.

[0003] Metallic Ru exhibits higher oxygen evolution reaction (OER) catalytic activity and lower cost compared to Ir. Therefore, various types of Ru-based catalysts have achieved significant progress in the field of acidic OER and hold promise as potential replacements for Ir-based catalysts. Many of these Ru-based catalytic materials exhibit high activity at 10 mA cm⁻¹. -2 At the specified current density, its catalytic activity surpasses that of commercial IrO2 and RuO2 catalysts. Its superior OER catalytic activity is beneficial for improving the efficiency of water electrolysis and promoting hydrogen production. Although Ru-based materials have made significant progress in the development of acidic OER electrocatalysts, their catalytic lifetime is unsatisfactory, generally stable for tens or hundreds of hours, at most a few hundred hours, which is difficult to meet the requirements of industrial applications. This makes the practical application of newly developed Ru-based catalysts to the anode of PEM electrolyzers a major challenge, greatly limiting the progress of PEM water electrolysis for hydrogen production in industry. Therefore, it is essential to develop efficient and stable Ru-based acidic oxygen evolution catalysts. Summary of the Invention

[0004] To address the problem of insufficient acidic oxygen evolution performance of existing Ru-based materials, this invention aims to improve the acidic oxygen evolution activity and stability of Ru-based materials by providing a RuO2-uniformly loaded WO3 self-supporting catalyst electrode, which exhibits excellent activity and high stability in acidic electrolytes.

[0005] The present invention discloses a method for preparing a RuO2-uniformly supported WO3 self-supporting catalyst electrode, which employs a stepwise hydrothermal-immersion-oxidation method, the steps of which are as follows:

[0006] (1) The substrate was immersed in a tungsten source aqueous solution, and WO3 nanowires in the form of nanorods were formed on the substrate by a one-step hydrothermal method.

[0007] (2) The WO3 nanowires obtained in step (1) are immersed in Ru source aqueous solution to adsorb Ru ions;

[0008] (3) The WO3 nanowires after adsorbing Ru ions in step (2) are oxidized in air to obtain a WO3 self-supporting catalyst electrode with uniform RuO2 loading.

[0009] In the above method, the tungsten source in step (1) is ammonium metatungstate, tungsten chloride, sodium metatungstate or sodium tungstate, the amount of tungsten source is 1 to 5 mmol, and the volume of the tungsten source aqueous solution is 30 to 100 mL.

[0010] In the above method, the Ru source in step (2) is ruthenium chloride, ruthenium acetate or ruthenium acetylacetonate, and the concentration of the Ru source aqueous solution is 0.5 to 20 mg / mL.

[0011] In the above method, the substrate in step (1) is carbon paper, carbon cloth, graphite sheet, titanium mesh or titanium sheet; it is used after being ultrasonically cleaned with acetone, ethanol and water in sequence.

[0012] In the above method, the temperature of the hydrothermal reaction in step (1) is 120-220℃ and the reaction time is 5-50h.

[0013] In the above method, the soaking temperature in step (2) is 25-80℃ and the soaking time is 1-50h.

[0014] In the above method, the oxidation temperature in step (3) is 200-450℃ and the oxidation time is 0.5-5h.

[0015] A RuO2-uniformly supported WO3 self-supporting catalyst electrode is prepared by the method described above. This RuO2-uniformly supported WO3 self-supporting catalyst electrode can be applied in acidic water cracking for oxygen desorption.

[0016] The present invention has the following beneficial effects:

[0017] 1. The present invention loads RuO2 material onto the surface of WO3, which can both make RuO2 uniformly distributed at the nanoscale and improve the stability of RuO2, and is a successful and universal preparation method;

[0018] 2. Compared with powdered catalysts, the present invention is an integrated self-supporting catalyst electrode, which does not require the use of polymer binders and will not peel off under working conditions;

[0019] 3. The catalyst electrode of this invention exhibits high electrocatalytic oxygen evolution activity and stability under acidic conditions: current density reaches 10 mA cm⁻¹. -2 At that time, the required overpotential is 203mV, and it can operate stably for more than 200 hours. Attached Figure Description

[0020] Figure 1 X-ray diffraction (XRD) pattern of the RuO2 uniformly loaded WO3 self-supporting catalyst electrode obtained in Example 1;

[0021] Figure 2 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the RuO2 uniformly loaded WO3 self-supporting catalyst electrode obtained in Example 1 are shown in Figure (a) and Figure (b), respectively.

[0022] Figure 3 Oxygen evolution polarization curves of commercial RuO2, carbon paper (CP) obtained in Example 1, and WO3 self-supporting catalyst electrode uniformly loaded with RuO2 (RuO2 / WO3) in 0.1M HClO4 electrolyte.

[0023] Figure 4 Oxygen evolution polarization curves of WO3 self-supporting catalyst electrodes with different proportions of RuO2 uniformly loaded in 0.1M HClO4 electrolyte obtained in Examples 1 and 3.

[0024] Figure 5 Stability curves of oxygen evolution in 0.1M HClO4 electrolyte for commercial RuO2 and WO3 self-supporting catalyst electrodes uniformly loaded with RuO2 obtained in Example 1 (RuO2 / WO3). Detailed Implementation

[0025] The present invention will be further described in conjunction with the embodiments and accompanying drawings. However, the scope of protection of the present invention includes, but is not limited to, the following embodiments. Any changes and adjustments made without departing from the spirit and scope of the present invention will also be included within the scope of protection of the present invention.

[0026] Example 1

[0027] (1) Cut carbon paper (CP) into strips with a length and width of 4cm*2cm, and clean them with acetone, ethanol and water in sequence for 10min each, and then dry them for later use.

[0028] (2) Weigh 5.912g (2mmol) of ammonium metatungstate, dissolve it in 40mL of deionized water, sonicate for 30 minutes to completely dissolve it, immerse the carbon paper substrate obtained in step (1) into the ammonium metatungstate aqueous solution, and then introduce it into the lining of a 50mL reactor. Hydrothermal treatment at 180℃ for 20h will yield WO3 nanowires that are uniformly grown on the carbon paper.

[0029] (3) The carbon paper with WO3 nanowires grown in step (2) was soaked in a 5 mg / mL RuCl3 (10 mL) aqueous solution and kept at 60 °C for 24 h to allow Ru ions to be adsorbed on the WO3 nanowires.

[0030] (4) The carbon paper with Ru ions adsorbed obtained in step (3) is placed in a muffle furnace and calcined at 400°C for 5 hours to obtain a WO3 self-supporting catalyst electrode with RuO2 uniformly loaded.

[0031] Some structural and property studies were conducted on the materials prepared by the above methods.

[0032] like Figure 1 As shown, the positions in this spectrum are assigned to RuO2 (PDF#40-1290) and WO3 (PDF#33-1387), indicating that the substance has a crystalline structure and contains both RuO2 and WO3.

[0033] like Figure 2 As shown, SEM reveals that the material is uniformly coated on the surface of carbon paper, while TEM shows the formation of RuO2 and WO3 heterostructures.

[0034] like Figure 3 As shown, carbon paper, commercial RuO2, and RuO2 / WO3 electrodes are used as anodes, with a working area of ​​1*1 cm. 2 A carbon rod was used as the counter electrode, a mercurous sulfate electrode as the reference electrode, and 0.1 M HClO4 was used as the electrolyte. The current density reached 10 mA cm⁻¹. -2 At that time, the required overpotentials for commercial RuO2 and RuO2 / WO3 were 272mV and 203mV, respectively, indicating that RuO2 / WO3 has higher oxygen evolution catalytic activity than commercial RuO2. It should be noted that the main cell of the electrochemical workstation is the external power source for the electrocatalytic oxygen evolution operation; the potentials obtained using mercurous sulfate as the reference electrode are all converted to reversible hydrogen electrode potentials in the property diagram.

[0035] like Figure 4 As shown, the oxygen evolution polarization curves of RuO2 / WO3 electrodes with different ratios in 0.1M HClO4 electrolyte are displayed, with current densities reaching 10 mA cm⁻¹. -2 At that time, the required overpotentials for RuO2-1 / WO3, RuO2-10 / WO3, and RuO2 / WO3 are 226mV, 215mV, and 203mV, respectively;

[0036] like Figure 5 As shown, at a current density of 10 mA cm⁻¹ -2 When the RuO2 / WO3 electrode can operate stably for more than 200 hours, it indicates that the self-supporting catalyst electrode has high catalytic activity and excellent catalytic stability under acidic conditions.

[0037] Example 2

[0038] Similar to Example 1, the content of ammonium metatungstate was changed to 1 mmol, 3 mmol, and 4 mmol. The overpotential was tested as in Example 1, and the RuO2-uniformly loaded WO3 self-supporting catalyst electrode achieved a current density of 10 mA cm⁻¹ in 0.1 M HClO₄ electrolyte. -2 The required overpotentials are 218mV, 235mV, and 250mV, respectively.

[0039] Example 3

[0040] Similar to Example 1, the RuO2 loading can be controlled by changing the RuCl3 concentration to 1 mg / mL (RuO2-1 / WO3) or 10 mg / mL (RuO2-10 / WO3). The overpotential was tested as in Example 1, and the catalyst achieved a current density of 10 mA cm⁻¹ in 0.1 M HClO4 electrolyte. -2 At that time, the required overpotentials are 227mV and 215mV, respectively.

[0041] Example 4

[0042] Similar to Example 1, the tungsten source was replaced with the same amount of sodium metatungstate. The overpotential was tested as in Example 1, and the catalyst achieved a current density of 10 mA cm⁻¹ in 0.1 M HClO₄ electrolyte. -2 At that time, the required overpotential is 276mV.

[0043] Example 5

[0044] Similar to Example 1, the ruthenium source was replaced with the same amount of ruthenium acetylacetone. The overpotential was tested as in Example 1, and the catalyst achieved a current density of 10 mA cm⁻¹ in 0.1 M HClO₄ electrolyte. -2 At that time, the required overpotential is 215mV.

[0045] Example 6

[0046] Similar to Example 1, carbon paper was replaced with carbon cloth. The overpotential was tested as in Example 1, and the catalyst achieved a current density of 10 mA cm⁻¹ in 0.1 M HClO₄ electrolyte. -2 At that time, the required overpotential is 232mV.

[0047] Example 7

[0048] Similar to Example 1, the carbon paper was replaced with a titanium mesh. The overpotential was tested as in Example 1, and the catalyst achieved a current density of 10 mA cm⁻¹ in a 0.1 M HClO₄ electrolyte. -2 At that time, the required overpotential is 208mV.

[0049] In summary, this invention employs a stepwise hydrothermal-immersion-oxidation synthesis strategy to achieve the preparation of a RuO2-uniformly supported WO3 self-supporting catalyst electrode. Benefiting from the synergistic effect between Ru and WO3 and the high conductivity of the substrate, this catalyst electrode material exhibits high activity in the acidic electrolytic oxygen evolution reaction. This catalyst electrode material exhibits low overpotential and long stability time in catalyzing the acidic electrolytic oxygen evolution reaction, and its preparation process is simple, using readily available and easily reproducible equipment, making it suitable for large-scale industrial production.

[0050] This invention discloses and proposes a RuO2-uniformly loaded WO3 self-supporting catalyst electrode, its preparation, and its application. Those skilled in the art can implement these methods by appropriately modifying conditions and routes, based on the content of this document. Although the methods and preparation techniques of this invention have been described through preferred embodiments, those skilled in the art can obviously modify or recombine the methods and technical routes described herein without departing from the content, spirit, and scope of this invention to achieve the final preparation technique. It is particularly important to note that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the spirit, scope, and content of this invention.

Claims

1. A method for preparing a RuO2-uniformly supported WO3 self-supporting catalyst electrode, comprising a stepwise hydrothermal-immersion-oxidation method, the steps of which are as follows: (1) The substrate is immersed in a tungsten source aqueous solution, and nanorod-shaped WO3 nanowires are formed on the substrate by a one-step hydrothermal method; (2) The WO3 nanowires obtained in step (1) are immersed in a Ru source aqueous solution to adsorb Ru ions; (3) The WO3 nanowires after adsorbing Ru ions in step (2) are oxidized in air to obtain a WO3 self-supporting catalyst electrode with uniform RuO2 loading.

2. The method for preparing a RuO2-uniformly supported WO3 self-supporting catalyst electrode as described in claim 1, characterized in that: In step (1), the tungsten source is ammonium metatungstate, tungsten chloride, sodium metatungstate or sodium tungstate, the amount of tungsten source is 1~5 mmol, and the volume of the tungsten source aqueous solution is 30~100 mL.

3. The method for preparing a RuO2-uniformly supported WO3 self-supporting catalyst electrode as described in claim 1, characterized in that: In step (1), the substrate is carbon paper, carbon cloth, graphite sheet, titanium mesh or titanium sheet; it is used after being ultrasonically cleaned with acetone, ethanol and water in sequence.

4. The method for preparing a RuO2 uniformly supported WO3 self-supporting catalyst electrode as described in claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 120~220℃ and the reaction time is 5~50 h.

5. The method for preparing a RuO2 uniformly supported WO3 self-supporting catalyst electrode as described in claim 1, characterized in that: In step (2), the Ru source is ruthenium chloride, ruthenium acetate or ruthenium acetylacetonate, and the concentration of the Ru source aqueous solution is 0.5~20 mg / mL.

6. The method for preparing a RuO2 uniformly supported WO3 self-supporting catalyst electrode as described in claim 1, characterized in that: In step (2), the soaking temperature is 25~80℃ and the soaking time is 1~50 h.

7. The method for preparing a RuO2 uniformly supported WO3 self-supporting catalyst electrode as described in claim 1, characterized in that: In step (3), the oxidation temperature is 200~450℃ and the oxidation time is 0.5~5 h.

8. A self-supporting catalyst electrode with RuO2 uniformly supported WO3, characterized in that: It is prepared by the method described in any one of claims 1 to 7.

9. The application of the RuO2 uniformly supported WO3 self-supporting catalyst electrode as described in claim 8 in acidic water cracking for oxygen desorption.